A platform with connections in many directions – further remarkable facets to the multifaceted methylbiquinoxen dication. Issue 10 (8th December 2016) - Leblanc, Nicolas; Genovese, Damiano; De Cola, Luisa; Powell, Annie K.
Abstract : New directions for the methylbiquinoxen platform. Abstract : The N, N ′-dimethyl-3, 3′-biquinoxalinium "methylbiquinoxen" dicationic platform is revealed to have even more fascinating possibilities than we originally thought in terms of its chemical versatility. In addition to its rich redox chemistry and coordination abilities, we have now unveiled an unexpected Lewis acid/base chemistry linked with a tuneable switching of its luminescence properties. This, amongst other things, allows for the facile fluorescent covalent labelling of hydroxyl-terminated materials. This platform provides intriguing chemical prospects realised in molecular systems such as porphyrins as well as an easy alternative functionalisation methodology to that provided by click-chemistry.